Molecular cloning and expression analysis of dmrt1 and sox9 during gonad development and male reproductive cycle in the lambari fish, astyanax altiparanae - Adolfi, Mateus C.; Carreira, Ana C O; Jesus, Lázaro W O; Bogerd, Jan; Funes, Rejane M.; Schartl, Manfred; Sogayar, Mari C.; Borella, Maria I. (BioMed Central, 2015)
Background: The dmrt1 and sox9 genes have a well conserved function related to testis formation in vertebrates, and the group of fish presents a great diversity of species and reproductive mechanisms. The lambari fish (Astyanax altiparanae) is an important Neotropical species, where studies on molecular level of sex determination and gonad maturation are scarce. Methods: Here, we employed molecular cloning techniques to analyze the cDNA sequences of the dmrt1 and sox9 genes, and describe the expression pattern of those genes during development and the male reproductive cycle by qRT-PCR, and related to histology of the gonad. Results: Phylogenetic analyses of predicted amino acid sequences of dmrt1 and sox9 clustered A. altiparanae in the Ostariophysi group, which is consistent with the morphological phylogeny of this species. Studies of the gonad development revealed that ovary formation occurred at 58 days after hatching (dah), 2 weeks earlier than testis formation. Expression studies of sox9 and dmrt1 in different tissues of adult males and females and during development revealed specific expression in the testis, indicating that both genes also have a male-specific role in the adult. During the period of gonad sex differentiation, dmrt1 seems to have a more significant role than sox9. During the male reproductive cycle dmrt1 and sox9 are down-regulated after spermiation, indicating a role of these genes in spermatogenesis. Conclusions: For the first time the dmrt1 and sox9 were cloned in a Characiformes species. We show that both genes have a conserved structure and expression, evidencing their role in sex determination, sex differentiation and the male reproductive cycle in A. altiparanae. These findings contribute to a better understanding of the molecular mechanisms of sex determination and differentiation in fish.
Keywords: DMRT1; Sex differentiation; SOX9; Spermatogenesis; Teleostei; Developmental Biology; Endocrinology; Reproductive Medicine